2014
DOI: 10.1177/147470491401200304
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Animals Capture and Maintain Attention in Humans

Abstract: Predation is a major source of natural selection on primates and may have shaped attentional processes that allow primates to rapidly detect dangerous animals. Because ancestral humans were subjected to predation, a process that continues at very low frequencies, we examined the visual processes by which men and women detect dangerous animals (snakes and lions). We recorded the eye movements of participants as they detected images of a dangerous animal (target) among arrays of nondangerous animals (distractors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 47 publications
10
71
0
1
Order By: Relevance
“…This result is in accordance with research indicating that dangerous predators such as snakes are identified by humans among fear-irrelevant distractors faster than vice versa (LoBue & DeLoache, 2008;LoBue & Rakison, 2013;Öhman et al, 2001). Furthermore, predators not only increase the visual attention of humans (Penkunas & Coss, 2013;Yorzinski et al, 2014), but young children seem to understand the harmful influences of predators on prey (Kubiatko, 2012). Barrett (2005), for example, demonstrated that when 4 -5-year-old children were asked to simulate an encounter between a predator and prey using plastic models, a majority of them correctly reported that "The lion eats the zebra" or "The zebra runs away from the lion".…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is in accordance with research indicating that dangerous predators such as snakes are identified by humans among fear-irrelevant distractors faster than vice versa (LoBue & DeLoache, 2008;LoBue & Rakison, 2013;Öhman et al, 2001). Furthermore, predators not only increase the visual attention of humans (Penkunas & Coss, 2013;Yorzinski et al, 2014), but young children seem to understand the harmful influences of predators on prey (Kubiatko, 2012). Barrett (2005), for example, demonstrated that when 4 -5-year-old children were asked to simulate an encounter between a predator and prey using plastic models, a majority of them correctly reported that "The lion eats the zebra" or "The zebra runs away from the lion".…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, detection of a snake among fear-irrelevant distractors (e.g., flowers, mushrooms) on a touchscreen was consistently faster than vice versa (LoBue & DeLoache, 2008;LoBue & Rakison, 2013;Öhman et al, 2001). Large carnivore predators are tracked by the eyes for a longer time than non-predatory animals (Penkunas & Coss, 2013;Yorzinski et al, 2014) and highly conspicuous, while aposematically coloured animals are detected by humans faster than nonaposematic animals (Bohlin et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, animals are visually preferred by two-day-old babies more than non-biological targets (Simion et al 2008) and are detected more rapidly than plants (Balas & Momsen, 2014). Predatory animals are detected faster than flowers or mushrooms (LoBue & DeLoache, 2008;Öhman, Flykt, & Esteves, 2001) and tracked by the eyes for a longer time than non-predatory animals (Penkunas & Coss, 2013;Yorzinski, Penkunas, Platt, & Coss, 2014). Observations by children and adults revealed that physical interaction with live animals was more frequent than with toys (LoBue, Bloom Pickard, Sherman, Axford, & DeLoache, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both pupils and adults, for example, detected the photos of snakes displaying a striking posture faster than the photos of resting snakes (Masataka, Hayakawa, & Kawai, 2011). It can be suggested that aggressive-looking pictures could attract more attention (Penkunas & Coss, 2013;Yorzinski et al, 2014) and stimulated situational interest enhanced information retention (Harp & Mayer, 1997;Hidi & Baird, 1988;Schraw & Lehman, 2001). This possibility can be further investigated by combining an eye-tracking technique with selfreports regarding interest in particular animals.…”
Section: Information Retention Concerning Aggressive-looking Animalsmentioning
confidence: 99%
“…Young American children also exhibited the precocious ability to detect a lion quickly in visual arrays of computer images of antelope and this ability does not differ appreciably from Indian children living in forests where leopards and tigers are present (cf. Penkunas & Coss, 2013 a,b;Yorzinski et al, 2014).…”
Section: Precocious Expression Of Antipredator Behaviormentioning
confidence: 99%